مسؤولية الطبيب الجنائية في الفقه الإسلامي والقانون الماليزي - Che Adenan Mohammad (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2005)
The study investigates a very important topic from the perspectives of Islamic jurisprudence (jiqh) and modem applied laws. It is a study of the medical doctors' criminal responsibility, within the context of Islamic jurisprudence and Malaysian law. The study aims to provide information about medical practices and legal aspects of these practices from the Islamic law perspective. It also focuses on criminal responsibility of medical doctors and identifies medical mistakes and the harm that patients may incur as a result of the practices of medical doctors; the study tries to establish the causal relationship between the two and identifies the similarities and differences in both Islamic and Malaysian law in dealing with these mistakes. An analytical methodology is adopted in this study by investigating related documents, and the collection of their jurisprudential quotations and citations, in search of the points of view of Islamic jurisprudence scholars. A comparative methodology is adopted in search of a relationship between Islamic and Malaysian law on the issue. The study then discusses the different scholars' points of view and identifies the acceptable points from the perspectives of these scholars and lawyers. One of the important conclusions of this study is that Islamic jurisprudence considers harm (danger) as the basis of human responsibility for criminal acts. The study also concludes that doctors' commitment - as acknowledged by Islamic jurisprudence and national law-must be viewed from the efforts they make and not from the result of their acts. Yet, this principle becomes weaker and undependable based on scientific development in medical methods and technology. Modern inventions have resulted in remarkable developments in the medical field to the extent that medical mistakes are considered rare and that recovery from illness is more attainable in this era. The study also concludes that the tenets of modem law on the issue are the same as those postulated by Islamic scholars thousand of years ago, thus the Islamic laws are suitable to deal with modern-day situations and cases relating to doctors' criminal responsibility. Thus maintaining that Islamic laws are appropriate and able to solve modern-day issues and problems of society.